2017
DOI: 10.1016/j.impact.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Detection and dissolution of needle-like hydroxyapatite nanomaterials in infant formula

Abstract: 20The unknowns surrounding presence, composition and transformations during the use 21 phase of engineered nanoparticles (ENPs) in consumer products raises potential human and 22

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 55 publications
2
18
1
Order By: Relevance
“…These aggregates can diverge markedly from spherical shapes and may even form highly branched or fractal structures, thereby fundamentally affecting transport properties and reactivities. Rates of particle dissolution, although known or experimentally measurable for many pure-phase nanomaterials in a welldispersed state (11,21), are challenging to predict for complex nanomaterial aggregates that have substantial internal surface areas with limited accessibility (22). Furthermore, these physical associations change as the nanomaterials encounter and transition through different local environments.…”
Section: Fundamental Properties Of Nanomaterialsmentioning
confidence: 99%
“…These aggregates can diverge markedly from spherical shapes and may even form highly branched or fractal structures, thereby fundamentally affecting transport properties and reactivities. Rates of particle dissolution, although known or experimentally measurable for many pure-phase nanomaterials in a welldispersed state (11,21), are challenging to predict for complex nanomaterial aggregates that have substantial internal surface areas with limited accessibility (22). Furthermore, these physical associations change as the nanomaterials encounter and transition through different local environments.…”
Section: Fundamental Properties Of Nanomaterialsmentioning
confidence: 99%
“…Many foods contain organic or inorganic nanosize particles, which may be present naturally in the food itself [ 1 , 2 ], be unintentionally generated during food processesing, or be introduced from the environment or packaging materials [ 3 7 , 2 ]. Engineered nanomaterials (ENMs) are also often added to commercial food products intentionally, exploiting the unique or enhanced properties of nanoscale particles relative to their larger counterparts in order to improve food quality, sensory appeal, shelf life or safety [ 8 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Delving deeper into the mechanistic study showed that the nano‐TiO 2 induced the EMT progression in colon cell through activation of TGF‐β and wingless (Wnt) pathways. We also identified other nanoparticles commonly used by food industry like silica nanoparticles (nano‐SiO 2 ) and hydroxyapatite nanoparticle (nano‐HA) which consumers could be ingesting for protracted periods of time, as inducers of the EMT process. The implications of our findings can be dire for many patients' (known and unknown) cases of colon cancer, as dietary nanoparticles may induce to hasten or even initiate the lethal cancer metastatic process toward the endothelium and thereafter other tissues.…”
Section: Introductionmentioning
confidence: 99%